2019
DOI: 10.1557/adv.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Si1-xGex layer on Si substrate by Screen-Printing

Abstract: The impact of the Al and Ge ratio in the Al-Ge pastes are investigated for fabricating the single crystalline Si1-xGex thick layers on large area Si substrates by screen-printing metallization process. From X-ray reciprocal space maps, Ge fraction in the fabricated Si1-xGex thick layers are found to increase up to 40% with increasing the Ge ratio in the Al-Ge pastes. On the other hand, the interface of the Si and Si1-xGex layers are getting winding with increasing the Ge ratio in the Al-Ge pastes. The Al-Si-Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…This method is a simple process using a conventional screen-printer and a furnace, and it has been confirmed that uniform SiGe layers with a thickness of more than 20 μm can be formed in a short processing time. [24][25][26][27][28] In this method, a liquid phase of Al-Ge-Si can be formed at a temperature below the mp of Si by screen-printing Al-Ge paste on a Si substrate. After the liquid phase is formed at high temperatures, cooling leads to the epitaxial growth of a SiGe layer at the interface of the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is a simple process using a conventional screen-printer and a furnace, and it has been confirmed that uniform SiGe layers with a thickness of more than 20 μm can be formed in a short processing time. [24][25][26][27][28] In this method, a liquid phase of Al-Ge-Si can be formed at a temperature below the mp of Si by screen-printing Al-Ge paste on a Si substrate. After the liquid phase is formed at high temperatures, cooling leads to the epitaxial growth of a SiGe layer at the interface of the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the formed SiGe layer have been found to strongly depend on fabrication parameters such as the Al/Ge ratio of the Al-Ge paste and the annealing temperature profile. 25,26,28) In this study, the effect of ambient gas during annealing on the growth of SiGe layers was investigated in order to determine the parameters of SiGe layer formation in liquid phase growth on Si substrates using Al-Ge paste.…”
Section: Introductionmentioning
confidence: 99%
“…The solar energy industry of crystalline silicon has more than 90% global marketing compared to other solar cells [1][2][3]. Single-junction devices perform ideally at a wavelength equivalent to the band gap, and lose efficiency at all other wavelengths over the sunlight based range [4].…”
Section: Introductionmentioning
confidence: 99%
“…The current global standard efficiency of silicon solar cells is limited to the range from 25% to 26.7% [5]. However, no decision is taken to scan for new options in contrast to solar cell structures that surpass this range [1]. To increase the efficiency of the singlejunction crystalline silicon cell with a single bandgap, some studies were made in the last several years on monocrystalline silicon solar cells fabricated by different techniques with thickness around 30 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, instead of conventional processes such as CVD and MBE, we have realized epitaxial growth of SiGe films having ~ 10 µm thickness by a process using original Al-Ge mixed pastes for screen printing on Si substrates and subsequent annealing in Ar ambient [27][28][29] . This method is a simple, low-cost, and high-speed approach that uses a melting point depression caused by the eutectic reaction, as seen in the Al-Si-Ge ternary phase diagram of Fig.…”
mentioning
confidence: 99%